Pendidikan Anak Berkebutuhan Khusus pada Anak Tunagrahita di Sekolah Inklusif Jenjang Sekolah Dasar - Susanti, Soneta Rahma; Ramadhani, Annisa (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to explore (1) the objectives of educating mentally retarded children in inclusive schools; (2) education of mentally retarded children in Inclusive Schools; (3) obstacles in the education of mentally retarded children in inclusive schools. The importance of inclusive education for children with special needs, especially the mentally retarded, in ensuring equal access to education for all individuals. This study uses the Systematic Literature Review (SLR) method to explore the education of mentally retarded children in inclusive schools. The results show that: 1) the aim of educating children with intellectual disabilities in Inclusive Schools is to help children with mild intellectual disabilities to receive equal education and support their growth; 2) education of mentally retarded children in inclusive schools requires the role of a teacher in adapting learning materials according to the needs of each individual in the class; 3) Barriers to the education of mentally retarded children in inclusive schools are differences in students’ levels of understanding and different learning needs, such as the ability to remember facts or concepts in learning.